A comparative study on machinability of cryo-treated and peak aged 15Cr-5Ni precipitation hardened stainless steel. (February 2018) - Palanisamy, D.; Senthil, P.
Highlights: Cryogenic and conventional heat treatment were done on solution treated samples. Microstructure and mechanical properties of all the three samples were analyzed. The effects of heat treatment and process parameters on machinability were studied. Comparatively the obtained surface finish was better for the cryo-treated samples. Tool wear was minimum for the solution treated sample than the cryo-treated sample. Abstract: Cryogenic treatment is a competent approach to improve the mechanical properties and microstructure of 15-5 PH stainless steel by considering the economic and other beneficial effects. This study brings out the correlation between the microstructure, mechanical properties and experimental examination on the machinability of 15-5 PH stainless steel. Cryogenic treatment with aging and conventional heat treatment process was done on the as received samples before machining. Mechanical properties and microstructure were evaluated at different treated conditions. This present investigation is to explore the effect of machining variables on performance measures namely tangential cutting force, tool wear, chip form analysis and surface roughness. The hardness and strength of cryogenically treated with aged samples were high while comparing with conventional heat treated samples. From the experimental investigation, it was observed that the cutting force and surface roughness are minimum at lower rate of feed and higher cutting speed for all the machined samples. The surface finish was found to be better for the cryo-treated with aged samples.